2004
DOI: 10.2174/1381612043453469
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Endothelial Cell Damage Via Nitric Oxide

Abstract: Vascular disorders, resulting from endothelial cell dysfunction, may be caused by various stimuli, including infectious pathogens, cytotoxic reagents, and pathophysiological mechanisms mediated by immune responses. Endothelial cell dysfunction characterized by apoptosis and abnormal immune activation is, at least in part, induced by anti-endothelial cell antibody (AECA) in some cases of autoimmune disease. However, the molecular mechanisms of AECA-mediated pathogenetic damage to host vascular system remain unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…We previously showed that anti-DV NS1 antibodies induced endothelial cell apoptosis by a NO-regulated pathway. 38,39 Other studies have reported the involvement of NO in hepatotoxicity, 34,[53][54][55] and that NO causes hepatocyte injury primarily by inducing apoptosis. 55,56 We found that dengue patient IgG-induced serum AST increase in mice was partially inhibited by NO synthase inhibitor L-NAME.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that anti-DV NS1 antibodies induced endothelial cell apoptosis by a NO-regulated pathway. 38,39 Other studies have reported the involvement of NO in hepatotoxicity, 34,[53][54][55] and that NO causes hepatocyte injury primarily by inducing apoptosis. 55,56 We found that dengue patient IgG-induced serum AST increase in mice was partially inhibited by NO synthase inhibitor L-NAME.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated the involvement of nitric oxide (NO) in anti-DV NS1-induced endothelial cell apoptosis. 38,39 Using NO synthase inhibitor N o -nitro-L-arginine methyl ester (L-NAME) to investigate its protective effect in liver injury, we found that dengue patient IgG-induced mouse serum AST increase was partially inhibited by L-NAME (Figure 6b).…”
Section: Liver Injury In Dengue Patient Sera Igg-treated Micementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, anti-endothelial cell Abs (AECAs) have been shown, at least partially, to be involved in vasculitis and endothelial cell dysfunction in patients with lupus, systemic sclerosis, thrombocytopenic purpura, and with microbial infections, such as dengue virus (DENV), hepatitis C virus, CMV, and group A Streptococcus (2-4). The vascular dysfunction induced by AECAs can be mediated through direct targeting to cell-surface autoantigens followed by stimulating or blocking their intracellular signaling, or indirectly linking to immune cells, such as neutrophils, monocytes, and NK cells to cause complement-and Ab-dependent cytotoxicity, as well as vessel inflammation (4)(5)(6). The mechanisms of autoantibody generation after autoantigen exposure are important issues to explore.…”
mentioning
confidence: 99%
“…Anti-DENV NS1 Abs cause inducible NO synthase (iNOS) expression and NO production in endothelial cells, which lead to NO-mediated cell apoptosis (4,26). Anti-DENV NS1 Abs also induce NF-kB-regulated inflammatory activation, including cytokine production and adhesion molecule expression (27).…”
mentioning
confidence: 99%